Oral Plaque from Type 2 Diabetic Patients Reduces the Clonogenic Capacity of Dental Pulp-Derived Mesenchymal Stem Cells - Antonella Bordin; Francesca Pagano; Eleonora Scaccia; Matteo Saccucci; Iole Vozza; Noemi Incerti; Antonella Polimeni; Elena Cavarretta; Isotta Chimenti; Elena De Falco (Stem Cells International)
Type 2 diabetes (T2D) is a major metabolic disease and a key epigenetic risk factor for the development of additional clinical complications. Among them, periodontitis (PD), a severe inflammatory disease ascribable to a dysregulated physiology and composition of the oral microbiota, represents one of the most relevant complications. Periodontitis can impact the structure of the tooth and likely the stem and progenitor cell pool, which actively contributes to the periodontal microenvironment and homeostasis. Modifications of the oral plaque play a key role in the etiopathogenesis of PD caused by T2D. However, to what extent the biology of the progenitor pool is affected has still to be elucidated. In this short report, we aimed to explore the biological effects of oral plaque derived from T2D patients with PD in comparison to non-diabetic patients with PD. Oral plaque samples were isolated from T2D and non-diabetic subjects with PD. Dental pulp stem cells (DPSCs), derived from the premolar tooth, were conditioned for 21 days with oral plaque samples and tested for their clonogenic ability. Cultures were also induced to differentiate towards the osteogenic lineage, and ALP and osteocalcin gene expression levels were evaluated by real-time qPCR. Results have shown that the number of clones generated by DPSCs exposed to T2D oral plaque was significantly lower compared to controls (ctl). The multivariate analysis confirmed that the decreased clonogenesis was significantly correlated only with T2D diagnosis. Moreover, the effect of T2D oral plaque was specific to DPSCs. Indicators of osteogenic differentiation were not significantly affected. This study provides a new biological insight into the effects ascribable to T2D in PD.